Biological activity and chemical characteristics studies of new oligomannose produced by Erwinia gerundensis - Shimaa K. Ali; F.M Mohamed; Ahmed H. El-Ghorab; Eman A. Hamed; Moustafa A. Aboel-Ainin; Mohamed A. Abdelgawad; Khaled El‐Adl; Hussein S. Mohamed (Carbohydrate Polymer Technologies and Applications)
Natural polymers have attracted considerable attention in recent decades among scientists due to their potential therapeutic uses, particularly as antimicrobial and antitumor agents. In this research, novel EPSs were extracted from garlic rhizosphere bacteria. The antibacterial and antitumor activities of the polymer were evaluated through biological assays. The antibacterial activity was tested against gram-positive microorganisms (such as Listeria monocytogenes, Bacillus cereus, and Staphylococcus aureus) and gram-negative organisms (such as Shigella sonnei and Escherichia coli). The most significant inhibition zone was observed with Listeria monocytogenes and S. typhi, measuring 35 mm, while the most miniature antibacterial effect was seen with Staphylococcus aureus at 23.67 mm.Furthermore, the inhibitory effect of the crude polymer was assessed using a broth medium with two strains of E. coli and Bacillus cereus. Electron microscope images displayed varying degrees of damage to bacterial cells in the treated broth. The antitumor activity was determined using the MTT test on colon carcinoma cells (HCT-116), hepatocellular carcinoma cells (HepG-2), and CaCO2 (intestinal carcinoma cells), with IC50 values of 188.86±6.17 µg/mL, 221.66±8.02 µg/mL, and 203.65±7.43 µg/mL, respectively, after 48 h. The bacteria responsible for polymer production were isolated from garlic plant rhizospheres and identified as Erwinia gerundensis CCASU-2024–69 through 16S rRNA sequencing. FTIR and NMR techniques determined the crude EPS's main components and functional groups, including carbonyl, carboxylic, methylene, and silanol. GC–MS analysis revealed 34 bioactive compounds, while HPLC analysis indicated that the EPS was a hetero-monosaccharide consisting of d-xylose, d-glucose, l-arabinose, ribose, and d-mannose. This research study represents the initial exploration into the exopolysaccharide derived from Erwinia gerundensis. To assess the interaction between the exopolysaccharide and the active sites of Bacillus cereus and E. coli, molecular docking experiments were conducted using five monosaccharides: d-xylose, d-glucose, l-arabinose, ribose, and d-mannose. The data obtained from the molecular docking analysis strongly correlates with the findings from biological studies.Furthermore, these highly active compounds exhibit a favorable proposed ADMET profile. This particular exopolysaccharide shows potential as a natural antibiotic and holds promise in treating gastrointestinal cancer. A comprehensive assessment of laboratory animals is essential before its potential use as a prebiotic in nutrition.